2015
DOI: 10.5713/ajas.14.0915
|View full text |Cite
|
Sign up to set email alerts
|

Energy Value of Cassava Products in Broiler Chicken Diets with or without Enzyme Supplementation

Abstract: This study investigated the metabolizable energy (ME) intake, net energy of production (NEp), heat production (HP), efficiencies of ME use for energy, lipid and protein retention as well as the performance of broiler chickens fed diets based on cassava chips or pellets with or without supplementation with an enzyme product containing xylanase, amylase, protease and phytase. The two products, cassava chips and pellets, were analysed for nutrient composition prior to feed formulation. The cassava chips and pelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
20
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 24 publications
4
20
1
1
Order By: Relevance
“…Result in the present study showed that feeding gathot decreased serum total triglyceride and abdominal fat content of broilers. This finding was slightly different from that reported by Bhuiyan and Iji (2015), in which inclusion of cassava pellet or cassava chip in broiler diets at up to 50 % (with enzyme supplementation) did not affect the abdominal fat weight of broilers. It has been reported that dietary fibre was responsible for the lowered serum triglyceride and abdominal fat content of broilers (Rama Rao et al 2005;Khempaka et al 2014).…”
Section: Discussioncontrasting
confidence: 83%
“…Result in the present study showed that feeding gathot decreased serum total triglyceride and abdominal fat content of broilers. This finding was slightly different from that reported by Bhuiyan and Iji (2015), in which inclusion of cassava pellet or cassava chip in broiler diets at up to 50 % (with enzyme supplementation) did not affect the abdominal fat weight of broilers. It has been reported that dietary fibre was responsible for the lowered serum triglyceride and abdominal fat content of broilers (Rama Rao et al 2005;Khempaka et al 2014).…”
Section: Discussioncontrasting
confidence: 83%
“…The lower weight of carcass, dressed weight and dressing percentage were due to the poor growth performance of these birds. The reason for the higher weight recorded for intestine with digesta may be partly due to delay in the digestion of cassava flour in the gastro-intestinal tract of the birds (Bhuiyan and Iji, 2015). The weight of crop with or without digesta reduced in birds fed on diets containing cassava flour.…”
Section: Resultsmentioning
confidence: 97%
“…Cassava is an important economic crop in the world, and it is widely cultivated in tropical and subtropical regions [1,2]. There are many uses of cassava, such as for food, animal feed, alcohol, biofuel, detergents, textiles, plastic, and other pharmaceutical products [3][4][5][6]. Due to the world population increasing, therefore, the global demand for cassava is also scaling up.…”
Section: Introductionmentioning
confidence: 99%